Perceptions of Ease, Usefulness and Promotion on Interest in Using ShopeePay Community Sumenep - Ninuk Isma Safitri; Arie Setyo Dwi Purnomo; Prasetyo Nugroho (Jurnal Manajemen Sains dan Organisasi, 2023)
Objectives – This study aims to analyze the impact of three key factors, namely perceived convenience, usefulness and promotion on interest in using ShopeePay as a digital payment tool. Design/Methodology/Approach – Quantitative type research and the population used is the Sumenep community of ShopeePay users. Data collection techniques by distributing google form questionnaires to 100 respondents directly. Findings – The results of the study indicate that the perception of convenience, usefulness and promotion has a positive and significant influence partial and simultaneous on the interest in using ShopeePay digital payments for the Sumenep community. Conclusions and Implications – Perception of convenience, perception of usefulness and promotion have a positive influence on the use of Shopeepay in the Sumenep community. Shopee companies can consider the convenience and usefulness of Shopeepay and can increase promotions to increase Shopeepay users in the Sumenep community.